ANALISIS TINGKAT KERUGIAN KEHILANGAN AIR PADA PROSES DISTRIBUSI SPAM UNS - Enggar Wahyu Wulaningtyas; Ferry Dimas Prakoso; Meidi Putri Ariyani; Muhammad Iriandru Pradipta; Yuniaristanto Yuniaristanto; Wahyudi Sutopo (Universitas Putera Batam, 2020)
As time goes by, there are more problems regarding the quantity and quality of water in Indonesia. One of these problems was found at Sebelas Maret University (UNS), precisely at Sistem Penyediaan Air Minum UNS (SPAM UNS). In serving its customers, SPAM UNS provides water tap and water dispenser facilities. However, there are still many weaknesses in the distribution of water. This is due to the frequent occurrence of pipe leaks and it takes a long time to find the location of the leak. As a result, financial losses experienced are quite large. The purpose of this study is to reduce losses by using the District Meter Area (DMA) concept to determine the area coverage (zoning) and the Analytical Hierarchy Process (AHP) method to determine the location of new reservoirs as a follow up of the zoning system. By implementing the DMA concept and the AHP method, SPAM UNS is able to reduce financial losses. The results obtained are making a new reservoir feasible because the value of the construction is almost the same as the initial loss value experienced by the UNS SPAM distribution network